Generalized Cesaro Summable Difference Sequence Spaces - Et, Mikail (E D P Sciences, 2017)
Et (M. Et, On some generalized Cesaro difference sequence spaces,. Istanbul Univ. Fen Fak. Mat. Derg. 55/56 (1996 97), 221-229) introduced Cesaro difference sequence spaces C-p(Delta(m)) (1 <= p < infinity), C-infinity(Delta(m)) and studied some topological properties. In this paper we continue to examine others relations with related the sequence spaces C-1(Delta(m)) and C-infinity(Delta(m)).
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Sets